Implantable cardioverter defibrillators in diabetics: efficacy and safety in patients at risk of sudden cardiac death. (August 2015) - Shahreyar, Muhammad; Mupiddi, Vijayadershan; Choudhuri, Indrajit; Sra, Jasbir; Tajik, Abdul Jamil; Jahangir, Arshad
<x xml:space="preserve">Abstract</x> Diabetes mellitus is a major risk factor for arrhythmogenesis and is associated with a two-fold increase in all-cause mortality and a four-fold increase in cardiovascular mortality including sudden cardiac death when compared with nondiabetics. Implantable cardioverter defibrillators (ICD) have been shown to effectively reduce arrhythmic death and all-cause mortality in patients with severe myocardial dysfunction. With a high competing risk of nonarrhythmic cardiac and noncardiac death, survival benefit of ICD in patients with diabetes mellitus could be reduced, but the subanalysis of diabetic patients in randomized clinical trials provides reassurance regarding a similar beneficial survival effect of ICD and cardiac resynchronization therapy in diabetics, as observed in the overall population with advanced heart disease. In this article, the authors highlight some of the clinical issues related to diabetes, summarize the data on the efficacy of ICD in diabetics when compared with nondiabetics and discuss concerns related to ICD implantation in patients with diabetes.